2016
DOI: 10.1039/c6ra04986a
|View full text |Cite
|
Sign up to set email alerts
|

Mg2Sn: a potential mid-temperature thermoelectric material

Abstract: The Mg2X (X = Si, Ge, and Sn) with X = Sn has the highest ZT value due to its large mass density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
5
14
0
Order By: Relevance
“…The trend of increasing carrier concentration with higher Sn content can be understood from the interplay between Fermi level and density of states or effective mass. Similar DOS shape and values for the VB have been reported [29,45,49,50], our results using hybrid-DFT, and with an exact-exchange mixing parameter of 25%, are shown in figures S1 and S2 of the SI. However, the VB-DOS close to the band edge differs between the two binaries, which determines the transport properties via the density of states effective mass (m * D ).…”
Section: Discussionsupporting
confidence: 85%
“…The trend of increasing carrier concentration with higher Sn content can be understood from the interplay between Fermi level and density of states or effective mass. Similar DOS shape and values for the VB have been reported [29,45,49,50], our results using hybrid-DFT, and with an exact-exchange mixing parameter of 25%, are shown in figures S1 and S2 of the SI. However, the VB-DOS close to the band edge differs between the two binaries, which determines the transport properties via the density of states effective mass (m * D ).…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we focus on Mg 2 Sn with the same crystal structure as Mg 2 Si. Mg 2 Sn has been studied extensively as a potential TE material [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . Xin et al 31 reported that an Sb-doped n-type polycrystalline Mg 2 Sn, Mg 2.15 Sn 0.98 Sb 0.02 exhibited a zT value of 0.53 at 650 K (κ and PF are 4.7 W/mK and 3.9 W/mK 2 , respectively).…”
mentioning
confidence: 99%
“…So to optimise the thermoelectric properties, main focus is the reduction of thermal conductivity. Due to the low lattice thermal conductivity, zT value of 1.1 was observed in p-type Mg 2 Sn at 800 K [192] which is more than Mg 2 Si(0.8) and Mg 2 Ge(1). The low lattice thermal conductivity is due to low velocity of optical modes caused by the large mass density [192].…”
Section: Sige Alloysmentioning
confidence: 95%
“…Due to the low lattice thermal conductivity, zT value of 1.1 was observed in p-type Mg 2 Sn at 800 K [192] which is more than Mg 2 Si(0.8) and Mg 2 Ge(1). The low lattice thermal conductivity is due to low velocity of optical modes caused by the large mass density [192]. zT reached the value of 0.46 in Mg2Si microstructure via Yb and Bi doping because Yb doping lowers the thermal conductivity and Bi doping adjusts the electronic transport properties [193].…”
Section: Sige Alloysmentioning
confidence: 95%